Metals valorization from pyrolyzed waste PCBS - Kilibarda Nikola B.; Kamberović Željko J.; Đokić Jovana M.; Kovačević Tihomir M.; Jovanović Nikola M. (Tehnika)
This paper examines the potential for valorizing the non-metallic fraction (NMF) of e-waste, focusing on metal recovery through pyrolysis to address challenges in electronic waste recycling. Characterization of a real sample showed that NMF contains 3.44 wt.% metals, primarily copper (80 wt.%), indicating potential for its valorization. Pyrolysis was optimized by varying temperature (up to 800°C) and atmospheric conditions (ambient vs. vacuum). The optimal oil extraction achieved at 700°C under vacuum. FTIR analysis identified phenols and halogenated aromatics in the generated oil. The pyrolyzed residue showed high concentrations of silver (494 g/t) and gold (56 g/t), enabling their further valorization. This research confirms NMF's dual potential for valorizing both organic and metal content, supporting sustainable material management.